D-dimer Levels in Acute, Medically Ill, Hospitalized Patients: A Large, Prospective, Multicenter Study in the United States - Jordan S. Richardson DO; Carol L. Clark MD; Aveh Bastani MD; Ali H. Shams MD; Gregory J. Fermann MD; Brian C. Hiestand MD; Bory Kea MD; Sharon E. Mace MD; W. Frank Peacock MD; Alex Yang MD; James A. Welker DO (Clinical and Applied Thrombosis/Hemostasis)
Background The study's main aim was to determine the prevalence of elevated D-dimer levels in adult patients hospitalized for acute medical illnesses not suspected to have venous thromboembolism (VTE). The secondary aims were to determine VTE prophylaxis rates and VTE events. Methods This multicenter, prospective, observational study included patients who were admitted across nine US hospitals. Patients who were ≥60 years of age, admitted for an acute medical illness (nonsurgical/nontraumatic), and not suspected to have VTE (deep vein thrombosis [DVT]/pulmonary embolism [PE]) were enrolled. Current use of anticoagulation and recent major surgery were exclusion criteria. D-dimers were measured at hospital admission, and the analysis was performed at a central laboratory using the STA-Liatest D-Di test kit (Diagnostica Stago, Asnières sur Seine, France). The upper limit of normal (ULN) for D-dimer was defined as ≥500 ng/mL. Age-adjusted thresholds were calculated as age × 10 ng/mL. VTE events included symptomatic DVT (distal or proximal) or PE occurring during admission. Results Among 995 patients (50.7% female; mean age, 70 ± 8 years), 74.4% (n = 740) had a D-dimer ≥ ULN, 62.2% (n = 619) had elevated age-adjusted levels, and 48.8% (n = 486) had D-dimers at least two times the ULN. The rate of VTE prophylaxis was 66.5% (n = 662); in this cohort, 1.8% (n = 18) developed a VTE. Conclusion Most hospitalized acute medically ill patients ≥60 years of age had elevated D-dimer levels on admission. Although an elevated D-dimer may be associated with VTE risk, its poor specificity indicates that it should not guide prophylaxis management without a multifactor risk assessment.